1997
DOI: 10.1063/1.364399
|View full text |Cite
|
Sign up to set email alerts
|

Control of the II–VI/GaAs interface reaction using hydrogen radical and Zn/As fluxes

Abstract: Strain effects and atomic arrangements of 60° and 90° dislocations near the ZnTe/GaAs heterointerface Appl.Local interface composition and extended defect density in ZnSe/GaAs(001) and ZnSe/In 0.04 Ga 0.96 As (001) heterojunctions J.The lifetime of II-VI-based blue-green laser diodes on GaAs substrates is limited by rapid degradation in the active layers. This degradation has been observed as dark defects in the active layer during the laser operation, where defects occurred due to stacking faults that origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…29 For temperatures raising from 250 to 450°C, the formation of Ga 2 Se 3 -like stoichiometry layers has been reported; except in the case where Zn-controlled passivation of the GaAs surface is made when ZnAs x compounds are formed. 30 Curiously enough, no equivalent photoemission study of the thermal stability of very thin ZnSe epilayers on GaAs has been published. We have only found the experimental study reported by Chen et al 26 for 5000-Å-thick ZnSe.…”
Section: Ga Out-diffusionmentioning
confidence: 99%
“…29 For temperatures raising from 250 to 450°C, the formation of Ga 2 Se 3 -like stoichiometry layers has been reported; except in the case where Zn-controlled passivation of the GaAs surface is made when ZnAs x compounds are formed. 30 Curiously enough, no equivalent photoemission study of the thermal stability of very thin ZnSe epilayers on GaAs has been published. We have only found the experimental study reported by Chen et al 26 for 5000-Å-thick ZnSe.…”
Section: Ga Out-diffusionmentioning
confidence: 99%
“…In recent years, many works have reported the formation of a Ga 2 Se 3 -type compound within the ZnSe/GaAs interface under specific growing conditions. 3,8,15,16 However, other investigators did not observe this phenomenon. 5,10,11 A study of the reconstruction process during the growth of crystalline Ga 2 Se 3 on GaAs substrates 17 proved the stability of this compound.…”
Section: Introductionmentioning
confidence: 89%
“…Another possible candidate for the transition layer is a Zn-As-type composition. 8,9 Despite the reported energetic instability of these compounds, 3 the presence of a thin ZnAs intermediate layer was detected in ZnSe/ GaAs epilayers 8,18 by a TEM method. Both models are dis-a͒ Present address: RIGAKU Corp., 3-9-12 Matsubara-cho, Akishima-shi, Tokyo 196, Japan.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations